O'ZBEKISTONDA TABIATNI MUHOFAZA QILISH AMALIYOTI - Ergashova Farangiz Oybek qizi; Qo'chqorov Javlon (Journal of new century innovations, 2022)
Annotation: in this article provides information about what actions are being taken in Uzbekistan today to protect the nature